Guest

If cos(a-b)+cos(b-c)+cos(c-a)=-3/... then prove that cosa+cosb+cosc=sina+sinb+sinc=0 and hence deduce that cos(a-b)=cos(b-c)=cos(c-a)=-1/2

If cos(a-b)+cos(b-c)+cos(c-a)=-3/... then prove that cosa+cosb+cosc=sina+sinb+sinc=0 and hence deduce that cos(a-b)=cos(b-c)=cos(c-a)=-1/2
 

Grade:11

1 Answers

Saurabh Koranglekar
askIITians Faculty 10336 Points
3 years ago
576-1964_1.PNG

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free